Outline-based geometric morphometric analysis to identify two Anopheles and three Culex mosquitoes in Thailand - TANAWAT CHAIPHONGPACHARA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Chaiphongpachara T. 2019. Outline-based geometric morphometric analysis to identify two Anopheles and three Culex mosquitoes in Thailand. Biodiversitas 20: 1866-1872. Geometric morphometric (GM) techniques have become popular for applications in entomology studies, especially mosquitoes. Outline-based methods (OTLs) are one such form of GM technique used to analyze pseudo-landmarks on contours or boundary outlines. This study investigated the efficacy of an OTL to distinguish two species of Anopheles mosquitoes including An. epiroticus and An. subpictus s.l. and three species of Culex mosquitoes, including Cx. quinquefasciatus, Cx. visnui and Cx. whitmorei in Thailand and compared outlines, including internal outline 1 (IOL1), internal outline 2 (IOL2) and external outline (EOL) within the mosquito wing to assess the optimal outline for analysis. The results indicated that OTLs were highly effective with certain species and each outline had the potential difference for identification. For size analysis, An. epiroticus had a mean perimeter length of IOL2 and EOL length larger than An. subpictus. Different sizes between species was found in IOL1, which was statistically significant after Bonferroni test (p < 0.05). Culex size analysis of IOL2 and EOL demonstrated a statistical difference for all species while size difference patterns between outlines found that IOL1 differed from other outlines. While shapes in two Anopheles of all cells were different between species, there was statistical significance based on Mahalanobis distances (p < 0.05). Almost all pairwise Mahalanobis distances between Culex species of IOL1, IOL2 and EOL established statistical differences, except for pairs of Cx. visnui and Cx. whitmorei via IOL2 analysis.